2018
DOI: 10.25304/rlt.v26.2035
|View full text |Cite
|
Sign up to set email alerts
|

Playful learning: tools, techniques, and tactics

Abstract: Over the past decade, there has been an increased use of playful approaches to teaching and learning in higher education. Proponents argue that creating 'safe' playful spaces supports learning from failure, management of risk-taking, creativity and innovation, as well as increasing the enjoyment of learning for many students. However, the emergent field of playful learning in adulthood is underexplored, and there is a lack of appreciation of the nuanced and exclusive nature of adult play. This article will fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
96
0
9

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(136 citation statements)
references
References 27 publications
1
96
0
9
Order By: Relevance
“…Panksepp et al demonstrated how rats can reflect their positive affective state by a 50-kHz ultrasonic vocalisation, i.e. rat laugher (Liu et al, 2017;Hirsh-Pasek et al, 2009;Whitton, 2018;Yogman et al, 2018). Extraordinarily, rough-and-tumble play in rats (a playful activity in which rats engage well into their adulthood) induces excessive laughter, which can lead to resilience against depression and anxiety, and facilitation of learning and memory (Burgdorf, Colechio, Stanton, & Panksepp, 2017).…”
Section: Physical and Mental Resiliencementioning
confidence: 99%
See 2 more Smart Citations
“…Panksepp et al demonstrated how rats can reflect their positive affective state by a 50-kHz ultrasonic vocalisation, i.e. rat laugher (Liu et al, 2017;Hirsh-Pasek et al, 2009;Whitton, 2018;Yogman et al, 2018). Extraordinarily, rough-and-tumble play in rats (a playful activity in which rats engage well into their adulthood) induces excessive laughter, which can lead to resilience against depression and anxiety, and facilitation of learning and memory (Burgdorf, Colechio, Stanton, & Panksepp, 2017).…”
Section: Physical and Mental Resiliencementioning
confidence: 99%
“…We argue that this growing discussion is taking place in parallel with the emergence of playful teaching approaches within higher education. These include many types of playful teaching, learning and academic practices (Whitton, 2018), and a signature pedagogy of playful learning in higher education (Nørgård et al, 2017). Although application remains both limited and privileged, this is considered to be a promising starting point for further development of 'Playful Universities' with 'Playful Curricula' and 'Playful Academics'.…”
Section: Potential Relevance For Higher Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as teachers' internet self-efficacy shapes their preferences regarding and professional adoption of the internet and related applications, their intentions in using the internet and enjoyment of the internet are related to their appreciation of its value. Teachers' intention to continue using the internet has been shown to affect their performance in internet-related instructional applications (Whitton, 2018). The internet's friendly human-machine interfaces attract early childhood educators who are willing to engage themselves and their students in the virtual interactions of our increasingly cybernetic world (Belo et al, 2016;Subramaniam, 2016).…”
Section: The Mediating Effect Of Early Childhood Educators' Enjoymentmentioning
confidence: 99%
“…Game architecture students build team cohesiveness in a mixed reality escape room game [45]. Educational escape rooms have been used by libraries for information search [6], team building [46,47] and also for school children [32].…”
Section: The Context and Design Of The Escape Roommentioning
confidence: 99%